ANALYSIS OF COLLABORATIVE SKILLS OF BIOLOGY EDUCATION STUDENTS SULTAN AGENG TIRTAYASA UNIVERSITY - Lestari, Iing Dwi; Rachmawati, Dian (Indonesian Journal of Educational Development (IJED), 2024)
Collaboration skills are essential for students to work effectively in teams, negotiate successfully, and make decisions collectively. This research analyzes the collaboration skills of Biology Education students at Sultan Ageng Tirtayasa University. The research methodology employed is quantitative descriptive analysis, which provides a comprehensive and detailed understanding of the students' collaboration skills. The research findings indicate that the average score for student collaboration skills was 84% in the outstanding category, 14% in the excellent category, and 1% in the sufficient category. The students scored 85 for indicators of positive interdependence, 84 for face-to-face interaction, 96 for individual personal accountability and responsibility, 89 for communication skills, and 91 for group working skills.